Ancient Christian commentary on Scripture ; OT v.III - Lienhard, Joseph T. (Downers Grove, IL IVP, 2001)
Contents : O.T. v. 3 : Exodus, Leviticus, Numbers, Deuteronomy. Includes bibliographical references and indexes.
Keywords: Bible. O.T. Exodus -- commentaries; Bible. O.T. Numbers -- commentaries; Bible. O.T. Deuteronomy -- commentaries; Bible. O.T. Pentateuch -- hermeneutics -- history -- early church, ca. 30-600.